Pengaruh Penerapan Green Accounting dan Good Corporate Governance Terhadap Kinerja Lingkungan dengan Profitabilitas Sebagai Variabel Moderasi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2021-2024 - Nasma Tia Miswari; Ramadona Simbolon; Shofwan Andri (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2026)
This study aims to analyze the effect of green accounting and good corporate governance on environmental performance and to examine the role of profitability in moderating these relationships among manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The study employed a quantitative approach using secondary data obtained from annual reports, sustainability reports, and PROPER data. The sample consisted of 16 manufacturing companies selected through purposive sampling, resulting in 64 observations. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that green accounting and good corporate governance have a positive and significant effect on environmental performance. Meanwhile, profitability, measured by Return on Assets (ROA), was unable to moderate the effects of green accounting or good corporate governance on environmental performance. These findings indicate that environmental performance is more strongly influenced by the implementation of environmental accounting and good corporate governance than by the level of company profitability.